Determining the Sources and Transport of Brown Carbon Using Radionuclide Tracers and Modeling. Issue 9 (10th May 2021) - Jiang, Hongxing; Li, Jun; Sun, Rong; Liu, Guoqing; Tian, Chongguo; Tang, Jiao; Cheng, Zhineng; Zhu, Sanyuan; Zhong, Guangcai; Ding, Xiang; Zhang, Gan
Abstract: The isotope tracer technique plays a key role in identifying the sources and atmospheric processes affecting pollution. The sources of brown carbon (BrC) at Guangzhou during 2017–2018 were characterized by positive matrix factorization with radiocarbon isotope constraints and multiple linear regression analysis. The primary emission factors of fossil fuel combustion (FF) and biomass burning (BB) accounted for 34% and 27% of dissolved BrC absorption at λ  = 365 nm (Abs365 ), respectively. The total mean light absorption contributed by secondary sources was 39%. The FF‐origin Abs365 changed insignificantly throughout the year and was dominant in the summer monsoon period, whereas the Abs365 from BB and secondary nitrate formation increased and contributed larger fractions during the winter monsoon period. Transported BrC was estimated using an index of 7 Be/( 7 Be + n 210 Pb). Higher values were generally accompanied by lower Abs365, whereas lower values were associated with higher Abs365, indicating that BrC absorption of aerosols transported from the upper‐atmosphere is lower than that of aerosols transported near the surface. Based on the positive correlations between 210 Pb and Abs365 and non‐fossil dissolved organic carbon in the winter monsoon period, we estimated that the contribution of invasive BrC (include ground and upper‐atmosphere level) to total absorption during the period of elevated BrC was ∼50%. The transported BrC was likely related to BB organic aerosols and secondary nitrate formation processes. This study supports radionuclides as a novel method for characterizing the sources and transport of BrC that can be applied in future atmospheric research. Key Points: 14 C‐constrained PMF model showed that fossil combustion, biomass burning and secondary sources contributed 34%, 27%, and 39% of total BrC absorption, respectively BrC absorption increased during winter with the transport of BBOA and secondary nitrates formation processes 210 Pb‐based estimation reveal that the transport BrC accounted for ∼50% of total BrC absorption during winter monsoon